2022
DOI: 10.1177/09544119221135688
|View full text |Cite
|
Sign up to set email alerts
|

Effect of whole-body vibration at different frequencies on the lumbar spine: A finite element study based on a whole human body model

Abstract: Many previous studies have found that occupational drivers commonly suffered from low back pain, and low back pain and degeneration of the intervertebral disc might be associated with vibration conditions. However, the biomechanical mechanisms of whole-body vibration that caused pain and injury were not clear. In this study, a validated whole human body finite element model was used, and vibration loads at frequencies of 3, 5, 7 and 9 Hz were loaded to evaluate the frequency effects on the spine. The results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…However, we still need to carefully explain the results of this study. Firstly, regarding the parameter settings of vibration therapy, some studies have reported that vibration close to the resonant frequency of the human body can cause damage to the spine [ 47 ] and that exposure to whole-body vibration in the work environment may lead to low back pain [ 48 ]. Kim et al [ 49 ] also concluded that there is a very strong correlation between irregular vibration and musculoskeletal disorders, especially the occurrence of LBP.…”
Section: Discussionmentioning
confidence: 99%
“…However, we still need to carefully explain the results of this study. Firstly, regarding the parameter settings of vibration therapy, some studies have reported that vibration close to the resonant frequency of the human body can cause damage to the spine [ 47 ] and that exposure to whole-body vibration in the work environment may lead to low back pain [ 48 ]. Kim et al [ 49 ] also concluded that there is a very strong correlation between irregular vibration and musculoskeletal disorders, especially the occurrence of LBP.…”
Section: Discussionmentioning
confidence: 99%
“…These results were consistent with some previous studies, 47,48 which indicated that the human body was more sensitive to low-frequency vibrations. The human body would produce large stresses and deformations under the vibration at resonance frequencies, 53 which may not be suitable for analysing the effects of multi-axial vibration. Therefore, the frequencies of the acceleration loads were chosen to be 2, 4 and 6 Hz to avoid resonance frequencies.…”
Section: Discussionmentioning
confidence: 99%